The alternative development: mision of the Nariño University for the life and peace - Erazo Coral, María Elena (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2020)
The objective Reflect on the alternative development that contributes to life and peace in the Region as a missionary project of the University of Nariño on the stage of the University Assembly. The originality of the research lies on approaching the issue from the regional logic to reflect upon its singularities, because there are multiple institutional missions, some of them look for contributing and solving the problems of capital and the market, and others, as the UDENAR case, they seek to contribute to the quality of life and peace of the region through the alternative development. Method: This research focused from the methodology of the non-simultaneity of the simultaneous, therefore the strategyapplied is the bibliographic and archive sources analysis through a matrix that establishes the regional and local particularities that focus the gaze of the homogenizing and universal inquiries, which allows to conclude: The University of Nariño, through the University Assembly, builds a mission and vision for alternative development under the principles of autonomy and democracy that entails a commitment to and for life and peace.